Simulation of inter and intra group behaviors using semantic virtual environments - Moura, Rafael Hocevar de (Pontifícia Universidade Católica do Rio Grande do Sul, 2013)
Made available in DSpace on 2013-08-07T18:43:14Z (GMT). No. of bitstreams: 1 000448558-Texto+Completo-0.pdf: 11790583 bytes, checksum: 8a3cb91e54cc3e1cb6d7eb3faf03b913 (MD5) Previous issue date: 2013 === Simulation of everyday situations from real life can be a very useful tool in entertainment applications and training systems. Such applications, as games or computer animated movies usually need to provide virtual environments populated with virtual autonomous agents. Commonly, the agents need to be able to evolve in their environment, avoiding collision with each other and obstacles, besides interacting with other characters in order to provide realistic simulations. This work presents a model to simulate coherent group behaviors based on procedural modeling and semantic environments. The main focus is to provide agents connected to the virtual environment they are evolving, mainly applied in the background of games or movies generated with few/without user intervention. === Simulação de situações cotidianas da vida real pode ser uma ferramenta muito útil em aplicações de entretenimento e sistemas de treinamento. Essas aplicações, como jogos ou filmes de Computação Gráfica, normalmente precisam ter ambientes virtuais povoados com agentes virtuais autônomos. Geralmente, os agentes precisam ser aptos a evoluir no seu ambiente, evitando colisões com obstáculos e outros agentes, além de interagir com outros personagens a fim de reproduzir simulações realistas. Este trabalho apresenta um modelo para simular o comportamento de grupos de forma coerente, baseado em modelagem procedural e ambientes semânticos. O foco principal é simular agentes conectados ao ambiente virtual que eles estão evoluindo, que é principalmente aplicado em segundo plano nos jogos ou filmes, gerados com pouca ou nenhuma intervenção do usuário.